Neo-Hellenic poetry in Russia: Antonios Palladoklis (1747–1801) and Georgios Baldani (about 1760–1789) - Ermolaeva, Elena (Hyperboreus, 2019)
The article deals with the tradition of versiﬁcation in ancient Greek in Russia. The author looks at the work of two almost forgotten native Greek, Russian subject poets, Antonios Palladoklis and Georgios Baldani, who completed laudatory and occasional odes in ancient Greek with Russian poetic translations en regard for Empress Catherine II, Potemkin, the Orlovs and other nobles. After the Russian victories in the Turkish war (1768–1774) Greeks hoped that Catherine II would free Greece from Muslim Turks and restore Hellenism. The author provides a small selection of their poetry in ancient Greek with English translations. An amazing feature of the poems is their metrical variety: hexameters, elegiac couplets, Sapphic stanzas, iambic and Anacreontic dimeters, paroemiac, etc.